Power supply testing handbook - Crandall, Earl (Chapman & Hall, 1997)
Crandall's Power Supply Testing Handbook comes into the marketplace at an optimum time. Now, more than ever, there is an urgency for a comprehensive handbook on power supply testing that will fulfill the reference needs of the wide variety of professionals testing power supplies, including designers, manufacturers, purchasers, and field service organizations.